Seismic Response of Embedded Foundations in Inhomogeneous Soil - Ντούσκας, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Γεωτεχνικής. Εργαστήριο Εδαφομηχανικής, 2018)
In the present MSc thesis results of a three-dimensional finite-element study for the effect of embedment on the undrained bearing capacity, the elastic stiffness, and the seismic behaviour of square-in-plan foundations are presented for two linearly inhomogeneous soil profiles. For static analysis, equations for uniaxial horizontal (Q) and pure-moment (M) limit loads with the relative elastic stiffnesses (KHH and KMM) as functions of soil heterogeneity and embedment ratio are exported. Additionally, capacity envelopes for (QM), (NQ) and (NM) loading combinations are presented; special references for the significance of the vertical load (N) and the position of the reference point are noted. The response is affected by the type of contact between the foundation interfaces (vertical and horizontal) with the surrounding and underlying soil. For this reason, a comparison for two different soil-foundation interaction types is made; the ideal case of fully bonded contact [FBC] in contrast to tensionless and of limited shear (sliding) resistance interfaces [TSI]. Extensive comparisons are made with the results for homogeneous soil. One-dimensional seismic response of embedded foundations with a simple slender structure is investigated parametrically, as function of the foundation embedment ratio, the soil heterogeneity, the vertical safety factor and the superstructure slenderness. Diagrams of acceleration in various model positions, foundation settlement via rotation angle, loops M–θ for two seismic records are presented. Only [TSI] type of soil–foundation interaction interface is investigated. For credible results and conclusions, the system is subjected to two different seismic stimulations with various characteristics.